Treatment with interleukin‐33 is non‐toxic and protects retinal pigment epithelium in an ageing model of outer retinal degeneration. Issue 22 (20th October 2020) - Clare, Alison J.; Copland, David A.; Nicholson, Lindsay B.; Liu, Jian; Neal, Chris R.; Moss, Stephen; Dick, Andrew D.; Theodoropoulou, Sofia
Abstract: The leading cause of central vision loss, age‐related macular degeneration (AMD), is a degenerative disorder characterized by atrophy of retinal pigment epithelium (RPE) and photoreceptors. For 15% of cases, neovascularization occurs, leading to acute vision loss if left untreated. For the remaining patients, there are currently no treatment options and preventing progressive RPE atrophy remains the main therapeutic goal. Previously, we have shown treatment with interleukin‐33 can reduce choroidal neovascularization and attenuate tissue remodelling. Here, we investigate IL‐33 delivery in aged, high‐fat diet (HFD) fed mice on a wildtype and complement factor H heterozygous knockout background. We characterize the non‐toxic effect following intravitreal injection of IL‐33 and further demonstrate protective effects against RPE cell death with evidence of maintaining metabolic retinal homeostasis of Cfh +/−~HFD mice. Our results further support the potential utility of IL‐33 to prevent AMD progression.